2012
DOI: 10.1101/cshperspect.a008813
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Autophagy during Cell Survival and Cell Death

Abstract: Autophagy is an important catabolic process that delivers cytoplasmic material to the lysosome for degradation. Autophagy promotes cell survival by elimination of damaged organelles and proteins aggregates, as well as by facilitating bioenergetic homeostasis. Although autophagy has been considered a cell survival mechanism, recent studies have shown that autophagy can promote cell death. The core mechanisms that control autophagy are conserved between yeast and humans, but animals also possess genes that regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
244
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(266 citation statements)
references
References 125 publications
2
244
1
7
Order By: Relevance
“…To avoid confusion with terms such as "autophagic cell death" (which is sometimes applied to states in which it is not clear that autophagy is required for cell death and/or in which autophagic features coexist with apoptosis or necrosis), we coined the term "autosis" to define cell death mediated by autophagy genes and characterized by focal perinuclear swelling. Although several studies have described cell death that is blocked by genetic inhibition of autophagy (6), such studies have not described increased substrate adherence and focal perinuclear swelling of dying cells. Thus, autosis represents a previously undescribed form of cell death by autophagy.…”
Section: Autophagy Peptide-induced Cell Death Has Unique Morphologicalmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid confusion with terms such as "autophagic cell death" (which is sometimes applied to states in which it is not clear that autophagy is required for cell death and/or in which autophagic features coexist with apoptosis or necrosis), we coined the term "autosis" to define cell death mediated by autophagy genes and characterized by focal perinuclear swelling. Although several studies have described cell death that is blocked by genetic inhibition of autophagy (6), such studies have not described increased substrate adherence and focal perinuclear swelling of dying cells. Thus, autosis represents a previously undescribed form of cell death by autophagy.…”
Section: Autophagy Peptide-induced Cell Death Has Unique Morphologicalmentioning
confidence: 99%
“…Autophagic cell death was originally defined as a type of cell death that occurs without chromatin condensation and is accompanied by large-scale autophagic vacuolization of the cytoplasm. This form of cell death, first described in the 1960s, has been observed ultrastructurally in tissues where developmental programs (e.g., insect metamorphosis) or homeostatic processes in adulthood (e.g., mammary involution following lactation or prostate involution following castration) require massive cell elimination (4)(5)(6). Autophagic cell death has also been described in diseased tissues and in cultured mammalian cells treated with chemotherapeutic agents or other toxic compounds (4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Normally cells activate autophagy (or macroautophagy) in times of nutrient deprivation to salvage critical nutrients essential for cell survival. By mechanisms still being worked out, autophagy targets proteins and organelles (such as the mitochondria) to the autophagosome, which then delivers the cargo to the lysosome for degradation and recycling of macromolecules (for review, see Chen and Klionsky 2010;Yang and Klionsky 2010;Das et al 2012). More than 30 different autophagy genes (ATGs) have been identified that regulate autophagy induction, cargo selection, vesicle formation, autophagosome fusion, cargo degradation, and release (for review, see He and Klionsky 2009).…”
Section: Mtorc1 Directly Regulates Autophagymentioning
confidence: 99%
“…1 In some circumstances, autophagy can promote an alternative form of cell death, such as in the clearance of larval tissues in Drosophila melanogaster. 2 As defects in autophagy have been implicated in several physiological and pathological conditions, such as cancer, neurodegenerative diseases, and aging, 3,4 it is important to obtain a complete understanding of the molecular mechanisms controlling autophagy.…”
mentioning
confidence: 99%